Conflict Resolution Ability in Late Bilinguals Improves With Increased Second-Language Proficiency: ANT Evidence - Novitskiy, Nikolay; Shtyrov, Yury; Myachykov, Andriy (Frontiers in Psychology, 2019)
Experimental data supporting the claim that bilingual speakers have superior cognitive control abilities are often questioned with respect to certain methodological limitations. One such limitation is the use of between-group design, potentially confounding bilingual status with other factors (e.g., socioeconomic status). Here, we used a homogeneous sample of 57 young adult Russian–English late unbalanced bilinguals who were administrated Attention Network Task (ANT) together with an L2 proficiency task. We tested the correlation of L2 vocabulary performance with conflict and alertness measures and overall reaction times in ANT performance. Overall, participants demonstrated better conflict resolution with the increase in their second language competence, with 8% of variance in conflict resolution explained by L2 proficiency. Our results support the notion of regular correspondence between bilingualism and cognitive control.